2020
DOI: 10.3389/fpsyg.2020.00144
|View full text |Cite
|
Sign up to set email alerts
|

Love, Work, and Striving for the Self in Balance: Anaclitic and Introjective Patients’ Experiences of Change in Psychoanalysis

Abstract: One of the most famous quotations credited to Freud is that, when asked what he thought a psychologically healthy person should be able to do, he said: "to love and to work." A central goal in psychoanalytic treatment is to bring about changes in basic, mostly unconscious, mental structures. The aim of this study was to investigate, applying an inductive thematic analysis, the experiences anaclitic and introjective patients have had of change after psychoanalysis with regard to the domains Love and Relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Extensive research has shown that personality characteristics influence what patients are looking for when seeking psychotherapeutic help, how they make use of therapy, and how helpful different forms of therapy are for them ( Blatt et al, 2001 ; Blatt and Shahar, 2004a , b ; Blatt and Luyten, 2009 ; Levander and Werbart, 2012 ; Werbart and Levander, 2016 ; Werbart et al, 2020 ). According to Blatt’s (2008) empirically supported theoretical “double helix” model, psychological development is a lifelong interplay between two basic dimensions in human experiences: the anaclitic orientation on interpersonal relatedness (ability to develop empathic, reciprocally attuned relationships) and the introjective orientation on self-definition (ability to establish a coherent, realistic, differentiated and positive sense of self).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has shown that personality characteristics influence what patients are looking for when seeking psychotherapeutic help, how they make use of therapy, and how helpful different forms of therapy are for them ( Blatt et al, 2001 ; Blatt and Shahar, 2004a , b ; Blatt and Luyten, 2009 ; Levander and Werbart, 2012 ; Werbart and Levander, 2016 ; Werbart et al, 2020 ). According to Blatt’s (2008) empirically supported theoretical “double helix” model, psychological development is a lifelong interplay between two basic dimensions in human experiences: the anaclitic orientation on interpersonal relatedness (ability to develop empathic, reciprocally attuned relationships) and the introjective orientation on self-definition (ability to establish a coherent, realistic, differentiated and positive sense of self).…”
Section: Introductionmentioning
confidence: 99%
“…They tend to keep others at a distance and make the best use of interpretative interventions in psychotherapy. Consequently, anaclitic patients seem to value and are more responsive to the quality of the therapeutic relationship, whereas introjective patients lay emphasis on increasing their understanding of themselves ( Blatt and Shahar, 2004b ; Blatt and Luyten, 2009 ; Levander and Werbart, 2012 ; Luyten and Blatt, 2013 ; Werbart and Levander, 2016 ; Werbart et al, 2017 , 2020 ; Hennissen et al, 2020 ). Anaclitic patients seem to benefit more from therapy with a greater relational focus on interaction in a face-to-face setting, where the therapist and patient can see one another, whereas introjective patients seem to benefit more from psychoanalytic therapy with a greater focus on insight and self-reflection, lying on the couch, where the patient does not see their therapist ( Blatt et al, 1988 , 2007 , 2010 ; Blatt, 1992 ; Blatt and Ford, 1994 ; Blatt and Shahar, 2004b ).…”
Section: Introductionmentioning
confidence: 99%